Remotely Temporal Scheduled Macrophage Phenotypic Transition Enables Optimized Immunomodulatory Bone Regeneration. Issue 39 (28th August 2022) - Huang, Donghua; Xu, Kaicheng; Huang, Xin; Lin, Nong; Ye, Yuxiao; Lin, Suya; Zhang, Jiamin; Shao, Jiaqi; Chen, Songfeng; Shi, Mingmin; Zhou, Xingzhi; Lin, Peng; et al.
Abstract: Precise timing of macrophage polarization plays a pivotal role in immunomodulation of tissue regeneration, yet most studies mainly focus on M2 macrophages for their anti‐inflammatory and regenerative effects while the essential proinflammatory role of the M1 phenotype on the early inflammation stage is largely underestimated. Herein, a superparamagnetic hydrogel capable of timely controlling macrophage polarization is constructed by grafting superparamagnetic nanoparticles on collagen nanofibers. The magnetic responsive hydrogel network enables efficient polarization of encapsulated macrophage to the M2 phenotype through the podosome/Rho/ROCK mechanical pathway in response to static magnetic field (MF) as needed. Taking advantage of remote accessibility of magnetic field together with the superparamagnetic hydrogels, a temporal engineered M1 to M2 transition course preserving the essential role of M1 at the early stage of tissue healing, as well as enhancing the prohealing effect of M2 at the middle/late stages is established via delayed MF switch. Such precise timing of macrophage polarization matching the regenerative process of injured tissue eventually leads to optimized immunomodulatory bone healing in vivo. Overall, this study offers a remotely time‐scheduled approach for macrophage polarization, which enables precise manipulation of inflammation progression during tissue healing. Abstract : This study fabricates a magnetic hydrogel to temporally regulate the immune microenvironment by the mechanical stimulation of magnetic field, which orchestrates the inflammation after injury and further optimizes the therapeutic functions. It provides a remote mode to precisely tailor the timing of controllable immunoreaction in order to achieve accelerated tissue regeneration.